A novel endovascular treatment for true ophthalmic aneurysms: A case report - Furst, Taylor; Mattingly, Thomas K.; Williams, Zoë R.; Schartz, Derrek; Bender, Matthew T. (Frontiers in Ophthalmology, 2022)
Introduction: Cerebral aneurysms located along the internal carotid artery at the origin of the ophthalmic artery can be treated through open surgery or endovascular technique. The former affords more certainty of aneurysm obliteration while the latter poses less risk to vision. Flow diversion is an increasingly accepted treatment for side-wall carotid aneurysms, although location at the branch point of the ophthalmic artery is known to moderate occlusion outcomes. Case Presentation: We present a case of a middle-aged female patient with a morphologically irregular 4mm OphA and a smaller superior hypophyseal aneurysm (SHA), whose successful obliteration by flow diversion with adjunctive coiling was predicted via a BTO. BTO was employed prior to stent placement to confirm (a) ophthalmic artery distal collateralization with external carotid artery (ECA) branches and (b) preserved arterial flow in the retina visualized via fundoscopy. Upon 1 year follow angiography, the patient suffered from no post-operative deficits and benefitted from complete occlusion of the OphA and SHA. Conclusion: OphAs constitute complex surgical disease that is historically associated with high visual morbidity. We present a novel advanced endovascular technique of BTO followed by flow diversion with adjunctive coiling that successfully obliterated an OphA while preserving vision.